2008
DOI: 10.1002/pd.2081
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis of Morquio disease

Abstract: A feasible strategy for PGD of Morquio disease including whole genome amplification by MDA and the use of preimplantation genetic haplotyping is described. MDA product archiving will be useful for future investigations if needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…20 Since then, other groups have introduced whole genome amplification, by a method called multiple displacement amplification (MDA), and indirect haplotyping into their PGD programmes. 22,23 Moreover, PGH has been applied in a number of other genetic and chromosomal disorders. 24 This new approach represents a major step forward in widening the scope and availability of PGD for serious mapped single-gene disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Since then, other groups have introduced whole genome amplification, by a method called multiple displacement amplification (MDA), and indirect haplotyping into their PGD programmes. 22,23 Moreover, PGH has been applied in a number of other genetic and chromosomal disorders. 24 This new approach represents a major step forward in widening the scope and availability of PGD for serious mapped single-gene disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was initially used to successfully haplotype and diagnose embryos for one couple with cystic fibrosis (MIM 219700) and one with Duchenne muscular dystrophy (MIM 310200) 20 . Since then, other groups have introduced whole genome amplification, by a method called multiple displacement amplification (MDA), and indirect haplotyping into their PGD programmes 22,23 . Moreover, PGH has been applied in a number of other genetic and chromosomal disorders 24 …”
mentioning
confidence: 99%
“…However, in a recent prospective cohort study, two-cell removal has been shown to negatively impact clinical outcome (De Vos et al, 2009). In our hands, removing two cells has been shown to increase the amplification efficiency of whole genome amplification (WGA) and reduce allele dropout (ADO) rate without affecting the pregnancy rates (Coskun et al, 2008).…”
Section: Biopsymentioning
confidence: 99%
“…Despite the fact that high ADO rates of PGD testing using MDA products derived from single cells could lead to misdiagnosis [34], the reliability of this approach has been demonstrated by many successful PGD protocols using single-cell MDA products provided that a sufficient number of STR markers are used [32,35,36].…”
Section: Introductionmentioning
confidence: 99%